Environmental cleaning to prevent COVID-19 infection. A rapid systematic review - Shimabukuro, Patrícia Mitsue Saruhashi (2020)
BACKGROUND: Faced with a pandemic, all healthcare actions need to reflect best practices, in order to avoid high transmissibility, complications and even hospitalizations. For hospital environments, the prod- ucts recommended and authorized by regulatory institutions for environmental cleaning and disinfection need to be highly effective. OBJECTIVE: To identify, systematically evaluate and summarize the best available scientific evidence on environmental cleaning to prevent COVID-19 infection. DESIGN AND SETTING: A systematic review of studies analyzing cleaning products that inactivate corona- virus, conducted within the evidence-based health program of a federal university in São Paulo (SP), Brazil. METHODS: A systematic search of the relevant literature was conducted in the PubMed, EMBASE, Co- chrane Library, CINAHL and LILACS databases, for articles published up to May 27, 2020, relating to studies evaluating cleaning products that inactivate coronavirus in the environment. RESULTS: Seven studies were selected. These analyzed use of 70% alcohol, detergent, detergent contain- ing iodine, household bleach, sodium hypochlorite, hydrogen peroxide, chlorine dioxide, glutaraldehyde, ultraviolet irradiation and plasma air purifier. The effectiveness of treating sewage with sodium hypochlo- rite and chlorine dioxide was also evaluated. CONCLUSION: Disinfection of environments, especially those in ordinary use, such as bathrooms, needs to be done constantly. Viral inactivation was achieved using chlorine-based disinfectants, alcohol, deter- gents, glutaraldehyde, iodine-containing detergents, hydrogen peroxide compounds and household bleaches. Alcohol showed efficient immediate activity. In sewage, sodium hypochlorite had better action than chlorine dioxide. REGISTRATION NUMBER: DOI: 10.17605/OSF.IO/YC5P4 in the Open Science Framework.